2021
DOI: 10.1039/d0cc07767d
|View full text |Cite
|
Sign up to set email alerts
|

Co, Fe codoped holey carbon nanosheets as bifunctional oxygen electrocatalysts for rechargeable Zn–air batteries

Abstract: CoFe@HNSs exhibited bifunctional oxygen electrocatalytic activity, and exhibit a high-power density of 131.3 mW cm−2 and long-term stability over 140 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…The high specific surface area will undoubtedly favor the exposure of more active sites and facilitate the mass transfer in the catalytic reactions. [36][37][38] The pore size distribution analysis (inset in Figure 2c) showed that the micropores (centered at 0.7 nm) and a small amount of mesopores and macropores coexist in FeÀ NÀ C/700 with a total pore volume up to 0.55 cm 3 g À 1 , proving the highly porous structures of the FeÀ NÀ C nanosheets. X-ray photoelectron spectroscopy (XPS) was used to characterize the surface chemical composition and elemental bonding configuration of the samples.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The high specific surface area will undoubtedly favor the exposure of more active sites and facilitate the mass transfer in the catalytic reactions. [36][37][38] The pore size distribution analysis (inset in Figure 2c) showed that the micropores (centered at 0.7 nm) and a small amount of mesopores and macropores coexist in FeÀ NÀ C/700 with a total pore volume up to 0.55 cm 3 g À 1 , proving the highly porous structures of the FeÀ NÀ C nanosheets. X-ray photoelectron spectroscopy (XPS) was used to characterize the surface chemical composition and elemental bonding configuration of the samples.…”
Section: Resultsmentioning
confidence: 93%
“…As shown in Table S1, the specific surface areas of Fe−N−C/700‐Pre and Fe−N−C/700 were as high as 1087.8 and 952.6 m 2 g −1 . The high specific surface area will undoubtedly favor the exposure of more active sites and facilitate the mass transfer in the catalytic reactions [36–38] . The pore size distribution analysis (inset in Figure 2c) showed that the micropores (centered at 0.7 nm) and a small amount of mesopores and macropores coexist in Fe−N−C/700 with a total pore volume up to 0.55 cm 3 g −1 , proving the highly porous structures of the Fe−N−C nanosheets.…”
Section: Resultsmentioning
confidence: 93%
“…The fitted N 1s XPS peak is deconvoluted into four peaks referring to pyridinic N (398.2 eV), pyrrolic N (399.5 eV), graphitic N (401 eV), and oxidized N (402.5 eV), respectively (Figure 2b, Figure S6, Supporting Information). [ 29 ] As shown in Figure 2c, DAP‐HPNC‐1020 possesses a higher N content (4.12 wt%) than those of oPD‐HPNC‐1020 (1.85 wt%) and mPD‐HPNC‐1020 (3.62 wt%), which may be reasoned by the distinct composition of DAP in contrast with those of o‐Phenylenediamine (oPD) and m‐Phenylenediamine (mPD). 4.12 wt% of N content is a pretty high level in contrast with other reported N‐doped catalysts, the normal N content of which is around 2–4 wt%.…”
Section: Resultsmentioning
confidence: 99%
“…22 Despite signicant progress having been obtained in FeCo-based TMNC materials for the ORR by modulating composition and enlarging surface area, their mass activity is extremely low as the active sites are oen encapsulated within the carbon matrix during the pyrolysis process. Even though atomically dispersed Fe-N x /C and Co-N x /C moieties have sparked wide research interest recently in view of the maximized atomic efficiency, [24][25][26][27] the tedious preparation methods oen give rise to uneven metal distribution and aggregation. Considering that the ORR is a tri-phase (gas/liquid/ solid) process, hierarchically porous architectures with interconnected macro-/microchannels are essential for guaranteeing accessibility of active sites and accelerating mass transfer.…”
Section: Introductionmentioning
confidence: 99%